Utilization of Plantain Peel (Musa sapientum) and Sweet Potato Starch (Ipomea batatas) Waste in Combination with Glycerol Addition to Produce Biodegradable Plastic - Shafa Maura, Chika; Athariq, Muhamad; Mulmeyda, Rinda (Pusat Inovasi Sains, 2024)
Starch is a natural polymer derived from plants, known for its biodegradability, environmental friendliness, wide availability, and affordability. Glycerol, with its low molecular weight, serves as an effective plasticizer. Its addition enhances the physical and mechanical properties of plastics and provides protection against microbial degradation. This study aims to investigate the impact of glycerol addition on the mechanical properties of biodegradable plastics made from sweet potato starch and plantain peel waste. The research is an experimental to achieve this goal. The results indicated that all samples achieved 100% degradation, with elongation percentages ranging from 93.59% to 137.56%. The sample containing 10 grams of sweet potato starch and 5 grams of banana peel starch exhibited the lowest water absorption percentage at 73.43%. Additionally, the bioplastic sample consisting of 5 grams each of sweet potato starch and banana peel starch showed the highest thickness at 0.36 mm, meeting the established SNI standards. In conclusion, the mechanical properties, biodegradability, and transparency of bioplastics are influenced by variations in sweet potato starch and plantain peel starch composition, as well as by the addition of glycerol.